Pengaruh Motivasi Belajar Dan Kecerdasan Spiritual Terhadap Pelaksanaan Program Tahfidz Al-Qur’an Di SMP Negeri 1 Wungu Kabupaten Madiun - Alfin Taufiq Almujab; Moch. Mukhlison (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2019)
The implementation of the Tahfidz Al Qur'an program referred to in this study is a process or effort to remember the verses of the Holy Qur'an in memory and be able to maintain memorization of at least one juz during studying in grades 7 and 8 for students who take the Tahfidz program Al Qur'an in SMP Negeri 1 Wungu, Madiun Regency. The success or failure of the implementation of the Tahfidz Al Qur'an program is influenced by several factors, including learning motivation and spiritual intelligence. This research is a quantitative research. The population in this study were all students who took part in the Tahfidz program at SMP Negeri 1 Wungu, Madiun Regency, totaling 72 students. Data collection techniques use documentation, interviews and questionnaires. Data analysis techniques using multiple linear analysis, t test, F test, coefficient of determination, which is preceded by the assumption of the analysis test that is normality test and linearity test. The results of this study indicate that: 1) There is a significant positive effect on learning motivation towards the implementation of the Tahfidz Al Qur'an program. 2) There is a significant positive influence of spiritual intelligence on the implementation of the Tahfidz Al-Qur'an program. 3) There is a significant positive effect of learning motivation and spiritual intelligence together on the implementation of the Tahfidz Al Qur'an program.